AKTIVITAS ANTIOKSIDAN SEDUHAN DAUN KOPI KAWA KERING (Coffea arabica L) DENGAN METODE DPPH - Musyirna Rahmah Nasution; Martina Br Manullang (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Kawa Coffee is a traditional beverage made from coffee leaves which is a typical drink in Tanah Datar in West Sumatra. The dried kawa coffee leaves are brewed with hot water to produce a brownish color.Kawa coffee leaves (Coffea robusta L) containsecondary metabolites such as flavonoids. Flavonoids have been known to have antioxidant activity. Research has been conducted to determine antioxidant activity from steeping kawa coffee leaves using the DPPH method by spectrophotometry. The test concentrations used were 5%, 2.5%, 1.25%, 0.625%, 0.313%, 0.156%. The results showed that steeping dried kawa coffee leaves at a concentration of 5% had given DPPH radical inhibition of 87.036%. The IC50 obtained is 0.591%. Steeping kawa coffee leaves is a health drink that has strong antioxidant activity.